Respecting patient rights in perinatal care in the Podlaskie Voivodeship – introductory study - Kulesza-Brończyk, Bożena; Piekut, Krystyna; Sienkiewicz, Anna; Terlikowski, Sławomir J. (Polish Journal of Public Health, 2009)
Aim of the study. The study aimed to evaluate respecting of patients’ rights in obstetric hospitals in the Podlaskie Voivodeship Material and methods. The inquiry was carried out among 1000 women of public healthcare units in randomly chosen 9 hospitals. Results. Most of the examined patients positively evaluated the course of their labour and stay in hospital. The attitude of admision unit’s staff to patients was assessed as very kind and kind by 82% of the women. Very good treatment with respect to patients’ dignity was assured in the wards in 37% of the cases, in admision units – in 34%. Lack of privacy in admission units was reported by 23.5% of the surveyed patients. More than half of the surveyed women (53%) were not informed about the valid patient rights. Neonatological procedures in 39% were performed when a mother was absent. Conclusions. In the examined wards many positive procedures were reported, which testifies to the fact that their staff attempt at creating patient-friendly environment. In most cases violation of patient rights is connected with the violation of the right to privacy and dignity, the right to information, and the right to agree to medical procedures.